Variable Glycemic Responses to Intact and Hydrolyzed Milk Proteins in Overweight and Obese Adults Reveal the Need for Precision Nutrition. Issue 1 (4th January 2019) - Curran, Aoife M; Horner, Katy; O'Sullivan, Victoria; Nongonierma, Alice B; Le Maux, Solène; Murphy, Eoin; Kelly, Phil; FitzGerald, Richard J; Brennan, Lorraine
ABSTRACT: Background: Dietary modifications can contribute to improved pancreatic β cell function and enhance glycemic control. Objectives: The objectives of this study were as follows: 1 ) to investigate the potential of milk protein hydrolysates to modulate postprandial glucose response; 2 ) to assess individual responses; and 3 ) to explore the inter- and intraindividual reproducibility of the response. Methods: A 14-d randomized crossover study investigated interstitial glucose levels of participants in response to 12% w/v milk protein drinks (intact caseinate and casein hydrolysate A and B) consumed in random order with a 2-d washout between treatments. Milk protein drinks were consumed immediately prior to study breakfast and evening meals. Twenty participants (11 men, 9 women) aged 50 ± 8 y with a body mass index (in kg/m 2 ) of 30.2 ± 3.1 were recruited. Primary outcome was glucose levels assessed at 15-min intervals with the use of glucose monitors. Results: Repeated-measures ANOVA revealed that for breakfast there was a significant difference across the 3 treatment groups ( P  = 0.037). The ability to reduce postprandial glucose was specific to casein hydrolysate B in comparison with intact caseinate ( P  = 0.039). However, despite this significant difference, further examination revealed that only 3 out of 18 individuals were classified as responders ( P  < 0.05). High intraclass correlation coefficients were obtained for glucose response to study meals (intraclass correlation coefficient: 0.892 for breakfast with intact caseinate). The interindividual CVs were higher than the intraindividual CVs. Mean inter- and intraindividual CVs were 19.4% and 5.7%, respectively, for breakfast with intact caseinate. Conclusion: Ingestion of a specific casein hydrolysate successfully reduced the postprandial glucose response; however, at an individual level only 3 participants were classified as responders, highlighting the need for precision nutrition. Exploration of high interindividual responses to nutrition interventions is needed, in combination with the development of precision nutrition, potentially through an n -of-1 approach. This clinical trial was registered as ISRCTN61079365 (https://www.isrctn.com/ ).